2015
DOI: 10.3390/antibiotics4040643
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Monte Carlo Simulations to Optimize Institutional Empiric Antipseudomonal Therapy

Abstract: Pseudomonas aeruginosa is a common pathogen implicated in nosocomial infections with increasing resistance to a limited arsenal of antibiotics. Monte Carlo simulation provides antimicrobial stewardship teams with an additional tool to guide empiric therapy. We modeled empiric therapies with antipseudomonal β-lactam antibiotic regimens to determine which were most likely to achieve probability of target attainment (PTA) of ≥90%. Microbiological data for P. aeruginosa was reviewed for 2012. Antibiotics modeled f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
(27 reference statements)
0
9
1
Order By: Relevance
“…Our findings are also consistent with multiple previous Monte Carlo simulation studies, which showed that extended or continuous infusion of piperacillin/tazobactam is needed to achieve the 50% fT > MIC target at an MIC 16 mg/mL, particularly in patients with normal and augmented renal function. 25,[27][28][29] Of note, the prolonged infusion regimen of 3.375 g every 8 hours as a 4-hour infusion did not achieve optimal PTA in our study. We observed a PTA of 76.8% for patients with CrCl of 41 to 120 mL/min receiving this regimen.…”
Section: Discussioncontrasting
confidence: 62%
“…Our findings are also consistent with multiple previous Monte Carlo simulation studies, which showed that extended or continuous infusion of piperacillin/tazobactam is needed to achieve the 50% fT > MIC target at an MIC 16 mg/mL, particularly in patients with normal and augmented renal function. 25,[27][28][29] Of note, the prolonged infusion regimen of 3.375 g every 8 hours as a 4-hour infusion did not achieve optimal PTA in our study. We observed a PTA of 76.8% for patients with CrCl of 41 to 120 mL/min receiving this regimen.…”
Section: Discussioncontrasting
confidence: 62%
“…3 When group A streptococci are isolated, treatment should be changed to benzyl penicillin. 5,12 For gram-negative bacteria, an aminoglycoside (gentamicin) should be considered in addition to cephalosporins. 5,13 In immunocompromised patients, ampicillin/sulbactam or piperacillin/tazobactam may be required.…”
Section: Discussionmentioning
confidence: 99%
“…For fluoroquinolones, the PK/PD target was identified as achieving a peak concentration (Cpk) to MIC ratio of at least 10 [ 8 ]. These values were compared and validated with Monte Carlo simulations [ 17 , 21 , 22 ]. Additionally, MIC 50 and MIC 90 were calculated for comparison of results obtained with Etest ® with those from Vitek ® .…”
Section: Main Textmentioning
confidence: 99%